2020
DOI: 10.1016/j.neuroscience.2019.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Tuning GABAergic Inhibition: Gephyrin Molecular Organization and Functions

Abstract: To be highly reliable, synaptic transmission needs postsynaptic receptors (Rs) in precise apposition to the presynaptic release sites. At inhibitory synapses, the postsynaptic protein gephyrin self-assembles to form a scaffold that anchors glycine and GABA A Rs to the cytoskeleton, thus ensuring the accurate accumulation of postsynaptic receptors at the right place. This protein undergoes several post-translational modifications which control protein–protein interaction and downstream si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 119 publications
(153 reference statements)
1
45
0
1
Order By: Relevance
“…PSD-95 by its PDZ domains serves as a scaffolding protein with a docking site for signaling proteins clustering around NMDA-and AMPA-type glutamate receptors, which are crucial for excitatory neurotransmission and synaptic plasticity [34]. Gephyrin is a core scaffolding protein, the postsynaptic component of inhibitory synapses, and it controls the formation and plasticity of inhibitory synapses through regulation of GABAA and glycine receptors [35]. In the present study, we demonstrated that the levels of PSD-95 and gephyrin are modified in zebrafish models of DS.…”
Section: Discussionmentioning
confidence: 99%
“…PSD-95 by its PDZ domains serves as a scaffolding protein with a docking site for signaling proteins clustering around NMDA-and AMPA-type glutamate receptors, which are crucial for excitatory neurotransmission and synaptic plasticity [34]. Gephyrin is a core scaffolding protein, the postsynaptic component of inhibitory synapses, and it controls the formation and plasticity of inhibitory synapses through regulation of GABAA and glycine receptors [35]. In the present study, we demonstrated that the levels of PSD-95 and gephyrin are modified in zebrafish models of DS.…”
Section: Discussionmentioning
confidence: 99%
“…PSD-95, by its PDZ domains, serves as a scaffolding protein with a docking site for signaling proteins clustering around NMDA- and AMPA- type glutamate receptors, which are crucial for excitatory neurotransmission and synaptic plasticity [34]. Gephyrin is a core scaffolding protein, the postsynaptic component of inhibitory synapses, and it controls the formation and plasticity of inhibitory synapses through regulation of GABAA and glycine receptors [35]. In the present study, we demonstrated that levels of PSD-95 and gephyrin are modified in zebrafish models of DS.…”
Section: Discussionmentioning
confidence: 99%
“…Gephyrin contributes to the accumulation of GABA A receptors at postsynaptic sites by interacting with several key GABAergic synapse-specific proteins, enabling efficient inhibitory synaptic transmission ( Betz, 1998 ; Choii and Ko, 2015 ; Fritschy et al., 2008 ; Groeneweg et al., 2018 ; Pizzarelli et al., 2019 ; Tyagarajan and Fritschy, 2014 ). In addition, gephyrin is known to be required for synaptic clustering of glycine receptors (GlyRs) in the spinal cord and for molybdoenzyme activity in non-neuronal tissues ( Feng et al., 1998 ; Kirsch et al., 1993 ; Stallmeyer et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gephyrin is known to be required for synaptic clustering of glycine receptors (GlyRs) in the spinal cord and for molybdoenzyme activity in non-neuronal tissues ( Feng et al., 1998 ; Kirsch et al., 1993 ; Stallmeyer et al., 1999 ). Gephyrin is composed of three functional domains: an N-terminal G-domain, a central C-domain, and a C-terminal E-domain ( Choii and Ko, 2015 ; Kim et al., 2006 ; Pizzarelli et al., 2019 ; Sola et al., 2004 ). At postsynaptic sites, gephyrin assembles through G- and E-domain–mediated interactions into a complex submembranous lattice that is dynamically regulated by a number of posttranslational modifications and interactions with other binding proteins ( Choii and Ko, 2015 ; Groeneweg et al., 2018 ; Tyagarajan and Fritschy, 2014 ).…”
Section: Introductionmentioning
confidence: 99%